(untitled) (Open Herald: Periodical of Methodical Research, 2024)
The article presents fear, analysis of fear by scientists, situations that cause fear, phobias, types of phobias, the impact of phobias on the human nervous system, as well as important recommendations for parents, teachers and psychologists.